Social movements - Staggenborg, Suzanne (Oxford University Press, 2022)
Social movements are important means of bringing about political and cultural changes through collective action. The study of social movements helps us to understand how movements can achieve change, as well as how they are limited in doing so, by examining political and cultural opportunities and obstacles, organizational dynamics, resources, collective action frames, and strategies and tactics. The field of social movements is an exciting one, and scholars continue to produce new studies of a wide array of social movements in many different countries, while activists also regularly provide accounts of their experiences in social movements. Relevant to both activists and social scientists, the area is one that students find important and interesting. Given the proliferation of social movement scholarship in recent decades, it is a daunting task to attempt to capture the field in a short book. Thus, my goal is simply to introduce students and other readers to some interesting history, ideas, and questions about social movements. No single researcher can be an expert on all of the many social movements that might be covered in such a book, and I have limited myself to some of the movements that I have followed for many years in teaching and researching in the area. The book began with a Canadian edition, and later second and third Canadian editions, published by Oxford University Press Canada, which con-tain much more Canadian content. Some of this material, as well as material on other countries, remains in the American editions, but they include a lot more material on the United States. In the American editions of the book, I added a chapter on right-wing movements, which are particularly important in the United States. I also considered adding a chapter on the civil rights movement, which is obviously very important as well to the United States, but I decided instead to expand somewhat the material on the civil rights movement in my chapter on the protest cycle of the 1960s. My rationale for doing this instead of including a whole chapter on the civil rights movement is that there is so much excellent scholarship available on the movement that instructors can easily use to supplement my brief treatment. Hopefully, students will find this selection of contemporary protest movements interesting and will learn enough about theoretical ideas and approaches to movements to be able to apply this knowledge to other movements of interest"--